2001
DOI: 10.1093/carcin/22.6.913
|View full text |Cite
|
Sign up to set email alerts
|

Gene-environment interaction between an aldehyde dehydrogenase-2 (ALDH2) polymorphism and alcohol consumption for the risk of esophageal cancer

Abstract: Aldehyde dehydrogenase-2 (ALDH2) degrades acetaldehyde metabolized from ethanol. Its encoding gene ALDH2 has a functional polymorphism: ALDH2 Glu487LYS: An association between this polymorphism and esophageal cancer among alcoholics has been reported. To further evaluate the gene-environment interaction, a hospital-based case-control study was conducted. Cases were 102 patients with histologically confirmed esophageal cancer and controls were 241 non-cancer outpatients of Aichi Cancer Center. ALDH2 genotypes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(119 citation statements)
references
References 11 publications
8
105
1
1
Order By: Relevance
“…The frequencies of the ALDH2 Glu allele (wild-type) and the ALDH2 Lys allele (varianttype) in healthy controls were 75% and 25%, respectively, consistent with a previous study in an Asian population. 21 Compared with individuals who had the ALDH2 Glu/Glu or ALDH2 Glu/Lys genotypes, the crude OR for the ALDH2 Lys/Lys genotype was 2.60 (95% CI, 1.41-4.80), and the adjusted OR was 1.91 (95% CI, 0.96-3.80). The frequencies of the XRCC1 399Arg allele (wild-type) and the Gln allele (variant) were 61.5% and 38.5%, respectively, in the control group.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The frequencies of the ALDH2 Glu allele (wild-type) and the ALDH2 Lys allele (varianttype) in healthy controls were 75% and 25%, respectively, consistent with a previous study in an Asian population. 21 Compared with individuals who had the ALDH2 Glu/Glu or ALDH2 Glu/Lys genotypes, the crude OR for the ALDH2 Lys/Lys genotype was 2.60 (95% CI, 1.41-4.80), and the adjusted OR was 1.91 (95% CI, 0.96-3.80). The frequencies of the XRCC1 399Arg allele (wild-type) and the Gln allele (variant) were 61.5% and 38.5%, respectively, in the control group.…”
Section: Resultsmentioning
confidence: 95%
“…23 Individuals with the ALDH2 Lys allele may have a high concentration of blood acetaldehyde after drinking alcohol. 24 The ALDH2 glutamic acid (Glu)/lysine (Lys) genotype, which encodes inactive ALDH2, enhances the risk for esophageal cancer in East Asian alcoholics. 25 Excessive alcohol consumption among smokers has been associated with an elevated risk of esophageal cancer.…”
mentioning
confidence: 99%
“…Cancer susceptible genes include types I and II metabolism enzyme genes, DNA repair gene and those affecting cell proliferation rate. In recent years, the evidence has been accumulated to support the hypothesis that cancer susceptible genes may be of importance in determining individual susceptibility to cancer [14][15][16][17][18][19] . EC is a disease determined by multi-factors, including environmental risk factors and genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…3 Most studies, conducted mainly in Japan, have revealed associations between the ADH2 or ALDH2 polymorphism and esophageal cancer risk. [4][5][6][7][8] Chao et al 9 found that Chinese alcoholic patients with the ADH2 G and ALDH2 A alleles were more susceptible to esophageal cancer. Wu et al 10 also found a multiplicative effect of lifetime alcoholic consumption and genotypes (ADH2 and ALDH2) on esophageal cancer risk, but those were only found in Taiwanese males.…”
Section: Introductionmentioning
confidence: 99%